RNA sequencing unravels the genetics of refractory/relapsed T-cell acute lymphoblastic leukemia. Prognostic and therapeutic implications - Gianfelici, V.; Chiaretti, S.; Demeyer, S.; Di Giacomo, F.; Messina, M.; La Starza, R.; Peragine, N.; Paoloni, F.; Geerdens, E.; Pierini, V.; Elia, L.; Mancini, M.; et al. (Haematologica (Roma), 2016)
Despite therapeutic improvements, a sizable number of patients with T-cell acute lymphoblastic leukemia still have a poor outcome. To unravel the genomic background associated with refractoriness, we evaluated the transcriptome of 19 cases of refractory/early relapsed T-cell acute lymphoblastic leukemia (discovery cohort) by performing RNA-sequencing on diagnostic material. The incidence and prognostic impact of the most frequently mutated pathways were validated by Sanger sequencing on genomic DNA from diagnostic samples of an independent cohort of 49 cases (validation cohort), including refractory, relapsed and responsive cases. Combined gene expression and fusion transcript analyses in the discovery cohort revealed the presence of known oncogenes and identified novel rearrangements inducing overexpression, as well as inactivation of tumor suppressor genes. Mutation analysis identified JAK/STAT and RAS/PTEN as the most commonly disrupted pathways in patients with chemorefractory disease or early relapse, frequently in association with NOTCH1/FBXW7 mutations. The analysis on the validation cohort documented a significantly higher risk of relapse, inferior overall survival, disease-free survival and event-free survival in patients with JAK/STAT or RAS/PTEN alterations. Conversely, a significantly better survival was observed in patients harboring only NOTCH1/FBXW7 mutations: this favorable prognostic effect was abrogated by the presence of concomitant mutations. Preliminary in vitro assays on primary cells demonstrated sensitivity to specific inhibitors. These data document the negative prognostic impact of JAK/STAT and RAS/PTEN mutations in T-cell acute lymphoblastic leukemia and suggest the potential clinical application of JAK and PI3K/mTOR inhibitors in patients harboring mutations in these pathways.